2011
DOI: 10.4103/0975-5950.94483
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of postextraction bleeding

Abstract: Vascular anomalies often affect the soft tissues though primary intraosseous lesions are uncommon. A 29-year-old patient reported to the Oral and Maxillofacial Surgery department of SCB Dental College, Cuttack, with the complaint of unusual bleeding from his extracted tooth socket. After undergoing routine hematological and radiological investigations and an angiogram, a diagnosis of arteriovenous malformation of the right posterior maxilla involving the posterior superior alveolar artery was established. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Arteriovenous malformations are high-flow lesions with direct communications between an artery (or arteries) and a vein (or veins), bypassing the capillary bed [ 3 ]. The earliest description of AVM was the reporting of snakes covering the Greek God Gordon's head.” [ 9 ]. Arteriovenous malformation of the head and neck is a rare vascular anomaly but when present is persistent and progressive in nature and can represent a lethal benign disease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arteriovenous malformations are high-flow lesions with direct communications between an artery (or arteries) and a vein (or veins), bypassing the capillary bed [ 3 ]. The earliest description of AVM was the reporting of snakes covering the Greek God Gordon's head.” [ 9 ]. Arteriovenous malformation of the head and neck is a rare vascular anomaly but when present is persistent and progressive in nature and can represent a lethal benign disease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the complications were present in the molars (60.0%) and females were more commonly affected by the complications than males. 11 In our study we found that 77.5% of patients had adequate knowledge of management of dry socket. The intern's capability of diagnosis of oroantral communication using blow test and their knowledge regarding treatments were checked in questions and we found that 70% of the interns were able to correctly mark the options given to them.…”
Section: Discussionmentioning
confidence: 53%